Digestibility and Physicochemical Properties of Brown Rice and Black Glutinous Rice under a Combination of Heat-Moisture Treatments and Citric Acid - Annisa Mawaddah; Endang Saepudin; Tuti Wukirsari (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2023)
Brown rice and black glutinous rice are rich in nutrients and fiber the body needs. The difference between brown and black glutinous rice lies in the starch content, namely amylose, and amylopectin, which can affect digestibility. Low digestibility rice can lower blood glucose levels, so it is needed for people with diabetes and obesity. This study modified brown rice and black glutinous rice with double modification HMT-crosslinking with citric acid and Crosslinking-HMT with various variations to determine the physicochemical properties and the lowest digestibility of brown rice and black glutinous rice. Multiple modifications can reduce digestibility, but a modification of HMT 25%-Crosslinking 20% showed the lowest digestibility in black glutinous rice. Differences in amylose and amylopectin levels in the sample can cause differences in the decrease in solubility and swelling power. The lowest solubility was found in brown rice with the HMT 25%-Crosslinking 20% variation, and the lowest swelling power in the brown rice sample with the HMT 25%-Crosslinking 20% variation. The formation of new covalent bonds after the crosslinking modification process can be identified by FTIR in the 1735 cm-1 regi